2021
DOI: 10.1039/d1cp00211b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of the formation of Ag nanoparticles assisted by PVP

Abstract: Understanding the formation mechanisms of nanoparticles is essential in the synthesis of nanomaterials with controlled properties. In solution synthesis, capping agents are used to mediate this process and control the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…Balankura, Yan [136] and Balbuena, Gianetti [137] also provided information related to the synthesis and aggregation of Ag nanostructures in the presence of PVP through MD simulations. In the case of Balankura, Yan [136], the aggregation mechanism of PVP-coated triangular Ag nanoplates in a vacuum and in the presence of ethylene glycol was analysed.…”
Section: Physics-based Models: Molecular Dynamics Simulations Of Agnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Balankura, Yan [136] and Balbuena, Gianetti [137] also provided information related to the synthesis and aggregation of Ag nanostructures in the presence of PVP through MD simulations. In the case of Balankura, Yan [136], the aggregation mechanism of PVP-coated triangular Ag nanoplates in a vacuum and in the presence of ethylene glycol was analysed.…”
Section: Physics-based Models: Molecular Dynamics Simulations Of Agnpsmentioning
confidence: 99%
“…This lower energy barrier was ascribed to the lower concentration of PVP found in the lateral faces of the surface of the NPs. Balbuena, Gianetti [137] investigated the nucleation and growth dynamic mechanisms of AgNPs in the presence of PVP and ethylene glycol. A detailed analysis of the complex steps that lead to NP formation was provided, and it was found that PVP does not have a significant influence on NP growth during the first ~0.1 𝑛𝑠.…”
Section: Physics-based Models: Molecular Dynamics Simulations Of Agnpsmentioning
confidence: 99%
“…A ideia de usar polímeros como agentes estabilizantes de nanopartículas partiu da adaptação do trabalho apresentado pelo alemão Hans Heinrich Helcher, em 1718, no qual foi verificada a estabilização de partículas de ouro utilizando amido, um polímero natural. 23 Desde então, muitos polímeros foram empregados para este fim, incluindo o poli(vinilpirrolidona) (PVP), 24,25 poli(álcool vinílico) (PVA) [26][27][28] e poli(etilenoglicol) (PEG). 27,29,30…”
Section: Polímero Como Molécula Estabilizadora De Partí-culasunclassified
“…These potentials are fit to give the bulk elastic constants, cohesive energy, low-index surface energies, and stacking fault energy. These potentials have been successfully used in other studies to simulate the mechanical behavior of nanostructures [30][31][32][33][34].…”
Section: 2mentioning
confidence: 99%